Cervical myelopathy caused by an exostosis of the posterior arch of C1 - Chooi, Yew Siong; Siow, Yew Siong; Chong, Chee Seang (The British Editorial Society of Bone & Joint Surgery, 2005)
We report a case of vertebral osteochondroma of C1 causing cord compression and myelopathy in a patient with hereditary multiple exostosis. We highlight the importance of early diagnosis and the appropriate surgery in order to obtain a satisfactory outcome.